Individualized Benefits and Access to Active Labor Market Programs Boost Refugee Women's Economic Integration - Bratu, Cristina; Martén, Linna; Ottosson, Lillit (The Review of Economics and Statistics, 2025)
Abstract The economic and social integration of refugees is a key policy concern and the situation of refugee women is particularly challenging, as many never enter the labor force. We study a reform of the Swedish integration program designed to tackle this issue by increasing women's participation in and access to active labor market programs. Using administrative data and a regression discontinuity design, we show that the reform resulted in lasting improvements in women's earnings and employment. We find no effects for men. Additional analyses suggest that individualizing financial benefits and early registration with the Public Employment Service are key mechanisms.